Software analysis for Agents of Things (AoT) applications - Mzahm A.M.; Ahmad M.S.; Tang A.Y.C.; Ahmad A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Application programs; Hardware; Intelligent agents; Internet; Internet of things; Multi agent systems; Reconfigurable hardware; Robotics; Spectrum analysis; Analytical process; Hardware configurations; Intelligent software; Intelligent software agent; Reasoning ability; Software ability; Software analysis; Value added service; Software agents